2022
DOI: 10.3389/fphar.2022.945971
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tranexamic acid for patients with intertrochanteric fractures treated with intramedullary fixation: A systematic review and meta-analysis of current evidence in randomized controlled trials

Abstract: Background: Tranexamic acid (TXA) has been widely applied to reduce perioperative bleeding. Recently, several studies focused on the administration of TXA in the treatment for with intertrochanteric fracture patients treated with intramedullary fixation. However, the efficacy and safety of TXA in these studies remain controversial. Therefore, we performed this systematic review and meta-analysis to investigate the efficacy and safety of TXA in intertrochanteric fracture patients treated with intramedullary fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…Thus, administering TXA at 3-h intervals postoperatively can sustain its effective concentration for an extended period, reinforcing coagulation functions during peak blood loss periods. Zhou et al [ 10 ] and Jiang et al [ 20 ] demonstrated the clinical efficacy of TXA appliances in reducing blood loss in IF, while ignoring the possibility of perioperative multiple doses of TXA. In our study, we compared the 3 different regimens and found 4-dose TXA therapy had excellent clinical effects in reducing perioperative blood loss compared to the single-dose group and control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, administering TXA at 3-h intervals postoperatively can sustain its effective concentration for an extended period, reinforcing coagulation functions during peak blood loss periods. Zhou et al [ 10 ] and Jiang et al [ 20 ] demonstrated the clinical efficacy of TXA appliances in reducing blood loss in IF, while ignoring the possibility of perioperative multiple doses of TXA. In our study, we compared the 3 different regimens and found 4-dose TXA therapy had excellent clinical effects in reducing perioperative blood loss compared to the single-dose group and control group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a systematic review and meta-analysis by Jiang et al investigated the efficacy and safety of TXA in IF patients treated with intramedullary fixation. The study included 9 randomized controlled trials with 972 patients, indicating that TXA significantly reduced total blood loss, intraoperative blood loss, hidden blood loss, and transfusion rate compared to the control group [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence consistently advocates for the use of TXA in controlling blood loss during TJA surgery, primarily attributing postoperative blood loss to the instantaneous activation of the fibrinolytic cascade ( 22 ). TXA's mechanism of action involves preventing fibrinolysis by blocking the lysine-binding site of plasminogen, thereby displacing plasminogen from the surface of fibrin ( 23 ). This synthetic fibrinolytic inhibitor competitively inhibits plasmin, plasminogen, and fibrin from combining, directly inhibiting plasmin activity ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…PRP consists of large amounts of growth factors and cytokines, which are released onto the wound and can recruit stem cells and various kinds of growth factors via cascade reactions. These cells and factors can contribute to regulating epithelial cell proliferation and migration, regulating fibroblastic activity [ 18 ], promoting angiogenesis and vessel permeability [ 53 ], and increasing protein and extracellular matrix synthesis [ 54 ]. In vivo, these growth factors could enhance the metabolic reprogramming of fibroblasts, especially promoting their glycolytic energy metabolism, to stimulate fibroblast proliferation and differentiation during tissue repairing [ 55 ].…”
Section: Discussionmentioning
confidence: 99%